Administered of Lavender (Lavandula Angustifolia) Aromatherapy To Improve Sleep Quality for the Elderly - Maharianingsih, Ni Made; Iryaningrat, A.A Sagung Istri; Brata Putri, Dhiancinantyan Windidaca (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2020)
Elderly people are age group with a higher incidence of disease or disorders than adults because of physical or psychological changes such as insomnia or decreased quality of sleep. Around 35 % of the total population decreased in sleep quality in the world and in Indonesia around 50%. Aromatherapy that using essential oils can be used as an alternative therapy besides drugs to treat sleep difficulties such as lavender Lavender contains linalool and linalyl acetate which can improve sleep quality and has a calming effect. The purpose of this study was to see the effect of lavender aromatherapy to improve sleep quality elderly. This research design used a pre-experimental design with one group pretest-posttest design method. Respondents were 42 elderly which taking with purposive sampling who resides in panti werda. Data analysis used a non-parametric test, namely the Wilcoxon test. The results obtained were that before using lavender aromatherapy there were 42 respondents (100%) who experienced a decrease in sleep quality. After giving lavender aromateraphy, 38 respondents (90.47%) experienced an increase in sleep quality and 4 respondents (9.53%) did not experience any changes, with p = 0.000. Improved sleep quality can be seen from the difference in the value of subjective sleep quality parameters, sleep latency, sleep duration, sleep efficiency, sleep disturbances, and daytime dysfunction based on the difference between the pretest and posttest scores. It can be concluded that giving lavender aromatherapy can improve the quality of sleep in the elderly.